Animal dietary exposure in the risk assessment of feed derived from genetically modified plants. (19th January 2023) - ,; Mullins, Ewen; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Moreno, Francisco Javier; Naegeli, Hanspeter; Nogué, Fabien; et al.
Abstract: EFSA carries out the risk assessment of genetically modified plants for food and feed uses under Regulation (EU) No 503/2013. Exposure assessment – anticipated intake/extend of use shall be an essential element of the risk assessment of genetically modified feeds, as required by Regulation (EU) No 503/2013. Estimates of animal dietary exposure to newly expressed proteins should be determined to cover average consumption across all the different species, age, physiological and productive phases of farmed and companion animals, and identify and consider particular consumer groups with expected higher exposure. This statement is aimed at facilitating the reporting of the information that applicants need to provide on expected animal dietary exposure to newly expressed proteins and to increase harmonisation of the application dossiers to be assessed by the EFSA GMO Panel. Advice is provided on the selection of proper feed consumption and feed concentration data, and on the reporting of exposure's estimates. An overview of the different uncertainties that may be linked to the estimations is provided. This statement also explains how to access an Excel calculator which should be used in future applications as basis to provide a more consistent presentation of estimates of expected animal dietary exposure.